Osmolalidade das soluções ativadoras com ou sem íons na ativação da motilidade do sêmen criopreservado de piabanha Brycon insignis (characiformes) - Motta, Naiara Cristina (2017)
The objective of this study was to determine the effect of activating solutions with different osmolalities, with or without ions, on the sperm quality of the cryopreserved sperm of Brycon insignis. The semen of 8 males was collected after hormonal treatment with carp pituitary extract. After collection, the semen was cryopreserved using methyl glycol as a cryoprotectant and a BTS™ solution was used as extender. The diluted sperm loaded into 0.5 mL straws, which were frozen in a nitrogen vapor vessel (dry shipper) and stored in a liquid nitrogen vessel. After five years the straws were thawed in a water bath at 60 °C for 8 seconds. In experiment 1, 11 solutions were prepared with reverse osmosis water (∼0 mOsm kg-1) and glucose or NaCl adjusted to an osmolality of 50, 100, 150, 200 and 250 mOsm kg-1. In experiment 2, 6 solutions were prepared with reverse osmosis water e NaHCO3, sodium citrate ((Na3C6H5O7), NaCl, KCl, CaCl2 or glicose (as an ion-free control), adjusted to ~98 mOsm Kg-1. The parameters of motility rate, curvilinear velocity (VCL), straight line (VSL), average path (VAP) and beat-cross frequency (BCF) of the post-thaw were determined using a Computer-Assisted Sperm Analyzer (CASA). Higher motility rates and velocities were observed in activated samples in NaCl and glucose solutions at osmolalities of 0 to 200 mOsm Kg-1, when compared to the activated samples in the solutions of 250 mOsm Kg-1 and was no statistical difference on motility rate and velocities between samples activated in NaCl or in glucose solutions within the same osmolality. The samples activated in NaHCO3, sodium citrate, NaCl, KCl or glucose presented the higher rates of motility, when compared to samples activated in CaCl2. Higher curvilinear velocities were observed in samples activated in NaHCO3, sodium citrate, KCl and glucose, when compared to samples activated in CaCl2. Samples activated in NaCl presented intermediate VCL values. The post-thaw sperm in B. insignis can be activated in ionic or non-ionic solutions with osmolalities of 0 to 200 mOsm/kg, however the CaCl2 solution should be avoided.